Site Specific Seismic Ground Response Analysis of Major Ports in Odisha, South-Eastern Coastal Region of India: A Case Study - Satyaprakash Mishra; Arjun Sil; Amit Kumar Das (Indonesian Journal on Geoscience, 2026)
Ports are vital economic arteries for any nation, making the resilience of port infrastructure to seismic events a paramount concern. This study emphasizes the necessity of constructing port facilities capable of withstanding significant seismic forces, particularly peak ground acceleration (PGA), which is crucial for maintaining their operational integrity during earthquakes. The local soil characteristics significantly influence the seismic ground motion, thus emphasizing the necessity of site-specific seismic investigations to enhance the safety of these critical structures. This study addresses the urgent need for site-specific seismic ground response analysis (GRA) in three major port locations in Odisha, India, where local geophysical data is scarce. Using borelog data and empirical correlations, shear wave velocity (Vs) profiles were estimated from standard penetration test (SPT-N) values. The analysis classified the sites based on their average Vs values at a depth of 30 m (Vs 30), following the criteria set by the National Earthquake Hazards Reduction Program (NEHRP). These were employed within the DEEPSOIL software framework to perform one-dimensional equivalent linear GRA using three real ground motion records representative of stable continental regions. The analysis computed peak ground acceleration (PGA), amplification factors, response spectra, and Fourier amplitude ratios. Results reveal significant amplification effects, especially at Dhamara port due to soft marine clays, with surface PGA values nearly doubling compared to bedrock input. Results show that surface-level PGA values are amplified up to 1.8 times the bedrock values, with the highest amplification at Dhamara. Fundamental site periods ranged from 0.47 to 0.72 s, and in some period ranges, the site-specific spectra exceeded IS 1893:2016 code spectra, particularly for Site Class E. The findings aid in the design of earthquake-resistant structures in regions where direct site-specific data may not be readily available, facilitating better-informed engineering decisions to enhance the resilience of port infrastructure against earthquakes.